Rural Cults and Urban Cults in Hellenistic and Roman Bithynia - Ferraioli, Ferdinando (ARYS. Antigüedad: Religiones y Sociedades, 2021)
The aim of this paper is to examine the principal evidences on cults in the rural and urban areas of Hellenistic and Roman Bithynia. The epigraphic dossier appears more limited for the Hellenistic period, while it is wider for the Roman one. The main divinities of the Greek cultic pantheon such as Zeus, Apollo, Artemis, Athena, Asclepius and others appear widespread in urban and rural areas; it is interesting how such deities in rural areas appear with local epithets of indigenous origin. Particularly interesting is the case of Zeus associated with the epithets Baleos and Okkonenos, which appear to be of Thracian origin, and Sabazios, which is probably of Phrygian origin. Other cults probably based on the mixture of Greek and non-Greek elements were that of the Great Mother Cybele, who had a temple dedicated to Nicomedia, and some local cults like Priettos, Tataula, Proustene and the Theoi Nerolenoi. In urban areas there are cults more linked to external influences such as Egyptian cults. This appears above all in coastal cities like Kios, Apameia and Nicomedia, which were already open to the cults of Isis and Serapis in the Hellenistic period. The influence of the Roman religion appears to be more limited and in a later period, as evidenced by the rare bilingual dedications and the attestation of the funeral rites of the Rosalia. The relationship between rural cults and urban cults appears therefore characterized by some differences, with rural areas appearing at least initially less willing to welcome foreign cults and more closely linked to indigenous cults. In the end, however, even in Bithynia, as has been noted for other areas of Asia Minor, there is, with the passage between the Hellenistic and Roman periods, a process of progressive integration between urban and rural cults, which probably takes place in a predominantly harmonious way and without major tensions between the various ethnic and territorial components.